Pengaruh GGG (Good Government Governance) dan Sistem Pengendalian Internal terhadap Kinerja Pemungutan Retribusi Sampah oleh Pemerintah Kota Gorontalo: Studi Kasus Dinas Lingkungan Hidup Kota Gorontalo - Alamri, Sakinah; Wuryandini, Ayu Rakma; Panigoro, Nurharyati (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of this research is to determine the effect of implementing Good Government Governance and the Internal Control System on the performance of waste levy collection by government officials at the Gorontalo City Environmental Service. This type of research is a quantitative method using multiple linear regression analysis. In the data collection technique, researchers distributed questionnaires to all officers in the Environmental Service, where the population for this study was 80 officers. The sampling technique used was purposive sampling with a research sample of 38 respondents. The partial test results in this study show that the variable (X1) Good Government Governance has no effect on the performance of collecting waste levies, the variable (X2) Internal Control System has an effect on the performance of collecting waste levies, whereas in the simultaneous test Good Government Governance and the Internal Control System have a positive effect on the performance of waste levy collection.